2002
DOI: 10.1300/j075v21n04_06
|View full text |Cite
|
Sign up to set email alerts
|

Using Public Feedback and Competitive Rewards to Increase the Safe Driving of Pizza Deliverers

Abstract: This study investigated the effects of a safe driving competition facilitated by publicly-posted individual feedback. The turn-signal use, safety-belt use, and complete intersection stopping of 82 pizza deliverers were observed at two experimental and three control stores, as well as among the civilian population. After baseline observations, pizza deliverers received posted weekly individual feedback on their turn-signal use (at Store A) or complete intersection stops (at Store B). The deliverers' safe drivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The results demonstrated that this type of normative feedback is more effective than averaged group feedback. In another study, Ludwig, Biggs, Wagner, and Geller (2001) paired normative feedback with an individual competition among pizza deliverers and demonstrated that even deliverers who did not win an award for their safe driving still changed their behavior during the program. However, there have been no individual monetary incentive program studies that allowed employees to see their peers' performance and incentives gained.…”
Section: Variations Of Feedback Within Incentive Programsmentioning
confidence: 99%
“…The results demonstrated that this type of normative feedback is more effective than averaged group feedback. In another study, Ludwig, Biggs, Wagner, and Geller (2001) paired normative feedback with an individual competition among pizza deliverers and demonstrated that even deliverers who did not win an award for their safe driving still changed their behavior during the program. However, there have been no individual monetary incentive program studies that allowed employees to see their peers' performance and incentives gained.…”
Section: Variations Of Feedback Within Incentive Programsmentioning
confidence: 99%
“…Behavioral safety interventions have been successfully implemented with a variety of worker populations, including roofers (Austin, Kessler, Riccobono, & Bailey, 1996), bus drivers (Olson & Austin, 2001), industrial plant workers (Sulzer-Azaroff, Loafman, Merante, & Hlavacek, 1990), and pizza deliverers (Ludwig, Biggs, Wagner, & Geller, 2001;. In a meta-analysis of 73 applications in a wide variety of industries, Krause, Seymour, and Sloat (1999) reported a 20% to 25% year-over-year decrease in injuries for the first 5 years after implementing a behavioral approach to safety.…”
mentioning
confidence: 99%
“…In contrast to Ludwig and Geller (1997), where pizza deliverers received group feedback, Ludwig, Biggs, Wagner, and Geller (2002) posted weekly individual feedback on either turn-signal use or complete intersection stops across different sites. Deliverers' percentages were posted individually on a vertical scale along with their names.…”
Section: Abstract Group Versus Individual Feedback Behavior-based Samentioning
confidence: 99%
“…There have been debates over the definitions and functions of response generalization (Austin & Wilson, 2002;Nouchins & Boyce, 2002). Because of this, Ludwig and Geller (Geller, 2002;Ludwig 2002;Ludwig & Geller, 2000) called for broadened ecological observations of both nontargeted behaviors and concurrent contingencies in Organizational Behavior Management (OBM) studies to build more databased examples of the phenomena. Accordingly, another objective of the current study was evaluating response generalization by observing nontargeted behaviors along with the behaviors targeted by the intervention.…”
Section: Abstract Group Versus Individual Feedback Behavior-based Samentioning
confidence: 99%